Search 72,392 tutors FIND TUTORS
Search for tutors
Ask a question

Answers by Philip N.

express the following in simplest radical form 4^(1/2)x^(1/6)y^(2/3) (answer)

Note that for any rational number k, y^(m/n) = y^(km/kn).  We know this because y^(m/n) = (y^(m/n))^(1) (Identity property of exponents) k/k = k * 1/k = 1 (Inverse property of multiplication) (y^(m/n))^(1) = (y^(m/n))^(k/k) (Substitution property of equality) [1] (y^(m/n))^(k/k)...

Determine rather the expression is a polynomial. -8x - 1/6x (answer)

It can be hard to type mathematical expressions here, but the second term in yours is ambiguous.  It could be either -8x - (1/6)x   (where the second term is the product of one sixth and x) or -8x - 1/(6x)   (where the second term is one divided by the product...

graph d=1.5+0.8t (answer)

The graph of this equation is a line.  We know that because each term is either a constant (1.5) or the product of a constant and the first power of a variable (d, 0.8t). Since we have two variables (d and t), the line sits in a two-dimensional plane, with a vertical axis and a horizontal...

6/10 min. = 8/ x min. (answer)

There are a number of ways to solve this.  Probably the simplest is to cross-multiply, using the ratios you've already set up. 6/10 = 8/x That implies 6×x = 8×10 6×x = 80 (6×x)/6 = 80/6 (6×x)/6 = 80/6 x = 13 1/3 minutes = 13 minutes, 20 seconds

An investor invested a total of $2,600 in two mutual funds. (answer)

Let A be the amount invested in Fund A, which earned 7%, and let B be the amount invested in Fund B, which earned 3%. We know that the sum of the amount earned from Fund A (7%×A) and the amount earned from Fund B (3%×B) is $138, or (7%×A) + (3%×B) = (0.07×A) + (0.03×B) = $138 [1] We...

Word problem for Algebra 9th grade (answer)

To solve this, we also need the other information from your other posting of this question. Up to Algebra 2: 38 Both:9 AP Calculus:? (https://www.wyzant.com/answers/9343/up_to_algebra_2_38__both9___ap_calculus) The students are divided into three groups: (a) those who entered...

Solve for n. A=nz+n (answer)

We can use the distributive property to factor the right side of the equation for n, and we get A = nz+n = n(z+1) Then, we can use the division property of equality to prepare to move z+1 to the left side of the equation and to isolate n. A/(z+1) = n×(z+1)/(z+1) Now,...